2009
DOI: 10.1007/s10620-009-1056-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atilmotin, a Motilin Receptor Agonist, on Esophageal, Lower Esophageal Sphincter, and Gastric Pressures

Abstract: Background Motilin, an endogenous gastrointestinal (GI) hormone, increases upper gastrointestinal tract motility and is associated with phase III of the gastric migrating motor complex. The motilin receptor agonist, atilmotin, at doses of 6, 30 or 60 µg intravenously (IV), increases the early phase of gastric emptying. Prior studies at higher doses of 100–450 µg IV demonstrated that some subjects developed noncardiac chest pain. Aims The aim of this study is to determine the effects of atilmotin on esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The latter are consistent with previous studies using human fundus from both obese and cancer patients, together with a more potent and much larger ability of motilin to facilitate cholinergic function in human gastric antrum . These data are also consistent with the ability of atilmotin to reduce human distal esophageal contractions while at the same time increasing muscle tension in the LES and proximal regions of the stomach . Similarly, intravenously administered 13 Nle‐motilin has been shown to facilitate muscle tension and cholinergic activity in human LES .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The latter are consistent with previous studies using human fundus from both obese and cancer patients, together with a more potent and much larger ability of motilin to facilitate cholinergic function in human gastric antrum . These data are also consistent with the ability of atilmotin to reduce human distal esophageal contractions while at the same time increasing muscle tension in the LES and proximal regions of the stomach . Similarly, intravenously administered 13 Nle‐motilin has been shown to facilitate muscle tension and cholinergic activity in human LES .…”
Section: Discussionsupporting
confidence: 91%
“…Finally, it is important to ask why motilin (and the motilin peptide atilmotin) inhibit esophageal movements in the present studies whereas some clinical studies with erythromycin report stimulatory activity (but not all; see Introduction for references). This is a difficult question to answer but three possibilities require discussion.…”
Section: Discussionmentioning
confidence: 87%
“…To support the inclusion of 12 subjects, for analysis of the primary endpoint, pre‐existing data are only available on the absolute LOS pressure rather than the change from baseline. Korimilli and Parkman have previously reported a between subject standard deviation (SD) of 8.05 mmHg, which we corrected by multiplying the between subject variance by (0.3/0.7) to give an estimate of the within subject variance, to derive an estimate of the within subject SD of 5.27 mmHg . From these data, we decided that a clinically meaningful difference between camicinal and placebo would be a 8.7 mmHg increase in LOS pressure.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to their prokinetic effects, marked controversy remains as to whether motilin agonists also have other physiological effect in the foregut . Therefore, the aim of this study was to evaluate the effect of camicinal on gastro‐physiological function.…”
Section: Introductionmentioning
confidence: 99%
“… 39 41 A manometric study has found that IBS patients exhibited significantly lower esophageal sphincter pressures compared with age and sex-matched controls. 39 Other researchers reveal a fluctuation among GI hormones, 42 glucose, 43 , 44 and oxidative free radicals 24 in patients with damages to the sphincters and smooth muscles. Interestingly, TCM formulae such as SNS exhibit consistent efficacy for maintaining the normal function of the sphincters, and thus may correct most, if not all, reflux-associated disorders.…”
Section: Discussionmentioning
confidence: 99%